Study of mortality and morbidity in patients with PCI vs CABG in cases of multivessel or left main disease in Tishreen University Hospital - الخير اياس (Latakia University Journal -Medical Sciences Series, 2022)
Ischemic heart disease is still the leading cause of death in the world and the optimal management is still disputed between interventional catheterization or surgical treatment in cases of multi vessel disease and left main lesion. Our study included 150 patients in the Catheter and Cardiac Surgery Department at Tishreen University Hospital who had multiple coronary injuries or left main lesion. 71 of them underwent interventional PCI and 78 of them underwent CABG. The results were better in the cardiac catheterization group when compared to the surgery group in terms of the development of cardiac and cerebrovascular accidents (MACCE), where the incidence of cardiac or cerebrovascular accidents in them was 11.3% compared to 18.9% in the group of patients with surgery (p = 0.001). As for mortality, when it was studied separately in both groups, there was no significant statistical difference of 2.2% in the catheterization group, compared to 3.7% in the surgical group (p=0.1). Thus, we conclude that the traditional indications of CABG are no longer the main determinant in decision-making, and we conclude that the modern generations of cardiac stents are superior to surgery in terms of overall results